Correlation of Social and Personal Identities: Current State of the Problem - E.P. Belinskaya (Социальная психология и общество)
The relationship between the features of personality identification structures and the characteristics of modern social space does not need detailed evidence. In the conditions of "fluid" modernity, the attention of researchers naturally shifts from the structural components of the "I" to the procedural manifestations of identity. As a result, the problem of the correlation of a person's personal and social identities, which is traditional for social psychology, begins to acquire a new sound.